2019
DOI: 10.1029/2019gc008577
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Structure of the Upper Crust From 0–75 Ma in the Equatorial Atlantic Ocean on the African Plate Using Ultralong Offset Seismic Data

Abstract: The uppermost oceanic crust composes of Layers 2A and 2B, and the boundary between them is debated to be a lava/dike transition or a hydrothermal alteration boundary within the lava unit. Here, we present the analyses of ultralong multichannel seismic data along a 1,500 km long profile covering 0-75 Ma of the oceanic lithosphere on the African plate in the equatorial Atlantic Ocean. We find that the Layer 2A is observed along the whole profile, with its P velocity increasing from 2.5 km/s near the ridge axis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 98 publications
4
29
1
Order By: Relevance
“…P ‐wave velocities at the top of basement in the study region increase from the ridge axis to ages of 58 Ma; this velocity increase is attributed to infilling of pore space during crustal alteration and provides evidence that hydrothermal circulation in the upper crust persists to 58 Ma (Kardell et al, 2019). A study in the equatorial Atlantic found that P ‐wave velocities at the top of seismic layer 2B (mean depth 820 m below sediment‐basement interface) increased to ages of 46 Ma, which is associated with hydrothermally circulating fluids extending to this depth and age (Audhkhasi & Singh, 2019). Studies on the Juan de Fuca ridge flank show that circulation through basement outcrops drives hydrothermal fluid movement, even when outcrops 50 km apart bracket seafloor with low‐permeability sediment cover (Fisher et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…P ‐wave velocities at the top of basement in the study region increase from the ridge axis to ages of 58 Ma; this velocity increase is attributed to infilling of pore space during crustal alteration and provides evidence that hydrothermal circulation in the upper crust persists to 58 Ma (Kardell et al, 2019). A study in the equatorial Atlantic found that P ‐wave velocities at the top of seismic layer 2B (mean depth 820 m below sediment‐basement interface) increased to ages of 46 Ma, which is associated with hydrothermally circulating fluids extending to this depth and age (Audhkhasi & Singh, 2019). Studies on the Juan de Fuca ridge flank show that circulation through basement outcrops drives hydrothermal fluid movement, even when outcrops 50 km apart bracket seafloor with low‐permeability sediment cover (Fisher et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 2,775 km of ultra‐deep reflection data was acquired along a stair‐like 2‐D profile (Audhkhasi & Singh, 2019; Mehouachi & Singh, 2018). Here, we focus our analysis and present results for one part of the data (∼250 km) collected along the line with a 347° azimuth sampling the region between the Romanche TF and ∼Charcot FZ, crossing the Chain FZ and propagator (Figure 1c).…”
Section: Methodsmentioning
confidence: 99%
“…The imaged Layer 2A/2B event is picked and depth converted. For the depth conversion we use a constant velocity of 4,000 m/s (Audhkhasi & Singh, 2019). .…”
Section: Transatlantic Ilab Mcs Data Setmentioning
confidence: 99%
“…As newly formed oceanic crust migrates away from the ridge axis it cools and subsides (Stein & Stein 1992;Hasterok 2013), primarily as a result of heat loss through hydrothermal circulation (Stein & Stein 1994) and, as sedimentation increases, thermal conduction (Fisher et al 2003). These processes alter the upper crust (Audhkhasi & Singh 2019) and effectively infill fractures, reducing porosity and permeability inherited at formation and during early development (Shaw 1994). Although this change is gradual, over time cracks are sealed and hydrothermal circulation becomes negligible.…”
Section: Introductionmentioning
confidence: 99%
“…Bratt & Solomon 1984;Collier & Singh 1998), two-dimensional profiles (e.g. Van Avendonk et al 1998;Audhkhasi & Singh 2019;Peirce et al 2019a,b;Wilson et al, 2019;Christeson et al 2020;Davy et al 2020), and three-dimensional tomographic grids (e.g. Toomey et al 1990;Gregory 2018;Robinson et al 2020;Simao et al 2020), that have become more detailed through the use of greater numbers of instrumentation deployed at smaller spatial intervals and able to sample at higher temporal rates.…”
Section: Introductionmentioning
confidence: 99%